Portugal : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by Executive Director for Portugal. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that a modest recovery is finally under way in Portugal. Growth rose to 1.3 percent in 2006, led by strong external demand, which is driving a notable rebound in export growth. In response, corporate investment shows signs of strengthening, but overall domestic demand remains relatively weak. Real GDP growth is projected to strengthen to about 1.8 percent in 2007 and 2008. Portugal's financial system remains sound and well supervised, and appears to have weathered the recent tensions in financial markets relatively well, though risks remain.